2009
DOI: 10.1029/2008ja013980
|View full text |Cite
|
Sign up to set email alerts
|

Dipolarization fronts as a signature of transient reconnection in the magnetotail

Abstract: [1] Dipolarization fronts (DFs), characterized by a strong and steep increase of the tail magnetic field component B z normal to the neutral plane and preceded by a much less negative dip of B z , are reported in many observations of bursty bulk flows and substorm activations throughout the whole Earth's magnetotail. It is shown that similar structures appear in full-particle simulations with open boundaries in a transient regime before the steady reconnection in the original Harris current sheet driven out of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
323
4
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 289 publications
(368 citation statements)
references
References 78 publications
(190 reference statements)
38
323
4
3
Order By: Relevance
“…It is well possible that additional destabilizing effects, such as the presence of nongyrotropic electrons arising from a local reduction of the normal field B z [Hesse and Schindler, 2001;Pritchett, 2005] or modified boundary conditions [Sitnov et al, 2002[Sitnov et al, , 2009Daughton et al, 2006;Divin et al, 2007], are necessary to turn the tail unstable. However, even then destabilization due to the presence of a multiscale equilibrium structure of the type discussed in this paper would play an important role, so that it has an essential favoring influence on the onset of magnetospheric substorms.…”
Section: Resultsmentioning
confidence: 99%
“…It is well possible that additional destabilizing effects, such as the presence of nongyrotropic electrons arising from a local reduction of the normal field B z [Hesse and Schindler, 2001;Pritchett, 2005] or modified boundary conditions [Sitnov et al, 2002[Sitnov et al, , 2009Daughton et al, 2006;Divin et al, 2007], are necessary to turn the tail unstable. However, even then destabilization due to the presence of a multiscale equilibrium structure of the type discussed in this paper would play an important role, so that it has an essential favoring influence on the onset of magnetospheric substorms.…”
Section: Resultsmentioning
confidence: 99%
“…Southnorth rotation of B z magnetic field component is often interpreted as a transient profile of a remote X-line due to its temporal change in the reconnection rate (Sergeev et al, 2005;Sitnov et al, 2009). Sormakov and Sergeev (2008) suggested that compression of the background magnetic field by a reconnected magnetic flux tube moving earthward can cause the bipolar variation of B z .…”
Section: Discussionmentioning
confidence: 99%
“…γ is the ratio of specific heats, P is the plasma pressure within the flux tube, and V = (1/B)ds is the volume of the flux tube containing 1 Wb of magnetic flux, where s is the length of the flux tube. They reflect the properties of reconnection regions they originate from and thus are of key importance for our understanding of magnetospheric substorm dynamics, and this is the reason why there is a plethora of studies investigating these plasma structures both theoretically/numerically (Sitnov and Swisdak, 2011;Nakamura et al, 2002;Birn et al, 2011;Sitnov et al, 2009;Guzdar et al, 2010) and observationally (Nakamura et al, 2001(Nakamura et al, , 2002Runov et al, 2009;Sergeev et al, 2009;Slavin et al, 2003a, b), just to mention but a few.…”
Section: Introductionmentioning
confidence: 99%
“…Dipolarization fronts, DFs, are tangential discontinuities in the magnetotail, separating the plasma sheet and fast plasma flows, which can be created by various mechanisms such as magnetic reconnection [Sitnov et al, 2009;Fu et al, 2012c] and kinetic interchange instability [Pritchett and Coroniti, 2011]. DFs are identified by a sharp increase of B z GSM and are associated with electron and ion acceleration [Asano et al, 2010;Zhou et al, 2010;Fu et al, 2011] as well as various wave activities, e.g., electron holes, whistler, lower hybrid, and electron cyclotron waves [Le Contel et al, 2009;Sergeev et al, 2009;Zhou et al, 2009;Deng et al, 2010;Khotyaintsev et al, 2011;Hwang et al, 2011].…”
Section: Introductionmentioning
confidence: 99%